MODELING SPATIAL VARIATION OF VEGETATION COVER DIVERSITY WITH THE HELP OF REMOTE LAND SOUNDING - Dychenko, O. Yu.; Laslo, O. O. (Scientific Progress & Innovations, 2020)
Methodical approaches have been developed for applying the data of remote sounding the Earth spectro- radiometer MODIS of Terra artificial satellite. It is visually possible to estimate a natural trend on phyto- mass increase throughout the spring period, and also the law of spatial distribution of front plant biomass increase. We can observe that in the southern areas, plant growth activation occurs earlier, than in the north. River valleys are also the zone of plant cover activity. In the end of spring, the distribution of NDVI index value becomes more evened owing to the vegetation beginning on agricultural lands. The analysis of the resulted data testifies that the general trend of NDVI index dynamics is similar in different types of plant cover. The index is minimal in the second half of winter, then there is an increase throughout all spring to the first half of summer then there is a gradual reduction till the end of autumn when the speed of decrease becomes more intensive. The derivative analysis allows to define more accurately the critical periods in veg- etation phenology. On the schedule of a derivative the maximum corresponds to the greatest local speed of phytomass, increase and a minimum – the greatest speed of phytomass decrease. The point of section with an axis of abscisses corresponds to the schedule extermums: a maximum, a minimum or an excess. The analysis of the received data testifies that against the general similarity of phytomass dynamics within administrative areas it is possible to establish the periods when the greatest differences between them are observed. Fea- tures of dynamics are most accurately shown at graphic of the displayed speeds of dynamics in time (deriva- tive) of NDVI index. So, the speed of decrease in phytomass in the end of the winter period essentially differs in various administrative areas. Differences are observed also at the beginning of the spring period which can be defined as a maximum rate of phytomass growth. The second peak marks the period of “agricultural spring” when crops actively grow. This period is accurately designated on schedules, but here areas differ a little. “Phenological summer” comes when the period of active accumulation of phytomass changes the pe- riod of its decrease. On the schedule of NDVI index, it is difficult to define precisely this period, and on the derivative schedule the corresponding point of section on an axis of abscisses is precisely defined. Accord- ingly, on indicators of phenological summer, essential differences between areas are observed. As a result of differences between areas which are established for dynamics of NDVI index it is possible to explain the pe- culiarities of a number of harmful insects dynamics. The landscape ecological diversity of the territory can be interpreted in terms of dynamics of plant cover. Each type of landscape cover forms specific time pattern of vegetation dynamics. Phenological dynamics under rather constant landscape conditions within the cer- tain time period can differ year from a year.